Practical linear precoder design for finite alphabet multiple-input multiple-output orthogonal frequency division multiplexing with experiment validation - Zheng, Yahong Rosa; Wang, Mingxi; Zeng, Weiliang; Xiao, Chengshan (IET communications, 2013)
A low complexity precoding method is proposed for practical multiple-input multiple-output (MIMO) orthogonal frequency-division multiplexing (OFDM) systems. Based on the two-step optimal precoder design algorithm that maximises the lower bound of the mutual information with finite-alphabet inputs, the proposed method simplifies the precoder design by fixing the right singular vectors of the precoder matrix, eliminating the iterative optimisation between the two steps, and discretising the search space of the power allocation vector. For a 4 × 4 channel, the computational complexity of the proposed precoder design is reduced to 3 and 6% of that required by the original two-step algorithm with quadrature phase shift keying (QPSK) and 8 phase-shift keying (8PSK), respectively. The proposed method achieves nearly the same mutual information as the two-step iterative algorithm for a large range of signal-to-noise ratio (SNR) region, especially for large MIMO size and/or high constellation systems. The proposed precoding design method is applied to a 2 × 2 MIMO-OFDM system with 2048 subcarriers by designing 1024 precoders for extended channel matrices of size 4 × 4. A transceiver test bed implements these precoding matrices in comparison with other existing precoding schemes. Indoor experiments are conducted for fixed-platform non-line-of-sight channels, and the data processing results show that the proposed precoding method achieves the lowest bit error rate compared with maximum diversity, classic water-filling and channel diagonalisation methods.